Analyzing the parallel program efficiency based on monitoring data - Nikitenko, D.A.; Stefanov, K.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
An approach to the analysis of parallel program efficiency is proposed on the basis of monitoring data available on Linux-based OS running parallel program. Some criteria of low efficiency and its classification are given. The results of a number of experiments are discussed.